Perceptions and attitudes of potential advertisers towards proposed outdoor boards in ITM / Mohd Adnan Hashim … [et al.] - Hashim, Mohd Adnan; Balong, Janet Jonathan; Abdul Aziz, Noor Azmawi; Hisham, Mohamad; Khalid, Norintan; Awang Madian, Dayang Salahah; Ibrahim, Manjalina; Ahmad Murad, Musalmah (1990)
The main campus of Institut Teknologi MARA (ITM) is evidently a large piece of land that boasts a community numbering close to 15,000 people. Over the years, its growth has been very encouraging, particularly in infrastructure development and student intake. With this progress, opportunities are abound for ITM to exploit its existing resources to earn some extra revenue. In simple words, we are proposing that ITM opens its doors to those who wish to advertise in the campus, the fees charged will be ITM's profit. With proper management, the potential advertisement sites around ITM could be put to good and profitable use. This study is conducted to find out the response of potential advertisers within the Shah Alam vicinity towards the possibility of buying advertisement space in the proposed outdoor boards in the campus. As it is, advertising serves as a useful function of informing the public about the existence and characteristics of a product, service or image.